1970
DOI: 10.1126/science.170.3961.986
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Lesions: Possible Pathogenetic Basis of the Generalized Shwartzman Reaction

Abstract: Evidence of vascular injury was found in rabbits after a single small dose of endotoxin from Escherichia coli. Eighty percent of the treated animals developed circulating endothelial cells, leukopenia, and thrombocytopenia, and 50 percent had aortic endothelial lesions as determined by electron microscopy. Prior anticoagulation with heparin did not prevent this response. No control animals showed these abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(40 citation statements)
references
References 13 publications
2
38
0
Order By: Relevance
“…Furthermore, the plasma levels of PA-inhibitor were unchanged (5). Moreover, the minimum dose of endotoxin capable of inducing a marked inhibitor response in vivo (10 ng/kg body wt) is at least two orders of magnitude lower than the dose shown to produce vascular lesions in rabbits (4,30).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the plasma levels of PA-inhibitor were unchanged (5). Moreover, the minimum dose of endotoxin capable of inducing a marked inhibitor response in vivo (10 ng/kg body wt) is at least two orders of magnitude lower than the dose shown to produce vascular lesions in rabbits (4,30).…”
Section: Discussionmentioning
confidence: 90%
“…Endotoxin-induced DIC is a multifactorial process that involves both cellular and humoral pathways (3). Endothelial cell damage with exposure of the subendothelial structures has been proposed as one of the main pathogenetic mechanisms (3,4). In addition, endotoxin-stimulated endothelial cells may trigger blood coagulation by producing procoagulant (thromboplastin-like) activity (5).…”
Section: Introductionmentioning
confidence: 99%
“…4). Thus, a distinct disturbance of vascular endothelium can be produced by endotoxin, as observed in brains of newborn kittens that developed PVL after endotoxin injection (122,164,165). Additionally, endotoxin has been shown to cause arterial hypotension in newborn dogs, in sublethal doses, and to produce in the same animals periventricular WM injury (166).…”
Section: Maternal/fetal Infection or Inflammation And Cytokine Releasmentioning
confidence: 99%
“…The authors concluded that circulating endothelium must have attached and proliferated to cover the suspended material. Gaynor et al 5 measured the number of circulating endothelial cells (CECs) in the blood of rabbits administered a dose of endotoxin, and reported an increase in the CEC concentration, which suggested that CECs could serve as a marker to measure vascular injury. Indeed, CEC concentrations have been found to be altered in patients with a variety of vascular injury and disease, including coronary angioplasty, 6 acute coronary syndromes and unstable angina, 7 peripheral vascular disease, 8 and inflammatory vasculitis, 9 when conditioning for bone marrow transplantation, 10 and during organ transplant rejection.…”
Section: Introduction and Initial Discovery Of Endothelial Progenitormentioning
confidence: 99%